(untitled) (DA NANG JOURNAL OF MEDICINE AND PHARMACY, 2026)
Introduction: Paragangliomas are neuroendocrine cell tumors originating from the neural crest and are classified as either adrenal or extra-adrenal. They are rare tumors that arise from sympathetic or parasympathetic paraganglia outside the adrenal glands. They may secrete catecholamines and present with non-specific clinical manifestations, often mimicking adrenal tumors. Objective:To report a case of paraganglioma located near the right adrenal gland that was sucessfully diagnosed and treated by transperitoneal laparoscopic surgery, and to highlight the challenges in preoperative diagnosis drawing clinical insights from the present case and a review of the literature. Methods: We report the case of a 51-year-old male with a history of hypertension and diabetes mellitus presenting with symptoms suggestive of catecholamine excess. A mass adjacent to the right adrenal gland had been detected incidentally three years prior through imaging studies. The patient underwent transperitoneal laparoscopic surgery for complete tumor resection. Results: The operation was performed safely, with a total operative time of 120 minutes and minimal blood loss. Histopathological examination confirmed the diagnosis of paraganglioma. The patient recovered well and was discharged after seven days without postoperative complications. Conclusion: Clinical examination combined with imaging modalities such as CT scans and Histopathological findings an important role in diagnosing extra-adrenal paraganglioma. Transperitoneal laparoscopic surgery is a minimally invasive method for treating paragangliomas located near the right adrenal gland.